Regulation of an Open Access Essential Facility - Manipushpak Mitra; Axel Gautier (University of Bonn, Bonn Graduate School of Economics (BGSE), 2003)
In this paper we consider the problem of regulating an open access essential facility. A vertically integrated firm owns an essential input and operates on the downstream market under the roof of a regulatory mechanism. There is a potential entrant in the downstream market. Both competitors use the same essential input to provide the final services to the consumers. The regulator designs a mechanism that guarantees financing of the essential input and adequate competition in the downstream market. We consider a regulatory mechanism that grants non-discriminatory access of the essential facility to a competitor. We show that this mechanism is welfare improving but it generates inefficient entry. That is a more efficient competitor may stay out of the market or a less efficient competitor may enter the market.
Keywords: L51; H54; D82; L11; 330; Regulation; Railways; Network; Entry; Competition; Access charge; Asymmetric Information; Eisenbahnpolitik; Deregulierung; Netzzugang; Potentieller Wettbewerb; Asymmetrische Information; Theorie